Exclusive Breastfeeding And Baby’s Growth And Development At Ages 7-12 Months - Hapsari, Retno N; Angelina, Zenia; Rihadi, Lukas S (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Introduction: Breastmilk is the main food source for babies. It contains optimal nutrition for baby's growth and development. World Health Organization (WHO) recommends exclusive breastfeeding is given for 6 months. According to Indonesian Health Profile data and information in 2017, babies who received ASI in Indonesian amounted to 35.73% and East Java at 34.92%. According to Basic Health Research in 2013, prevalence of stunting in children due to nutritional problems in Indonesia was 37.2% and in 2011 the rate of developmental disorders in infants was 13-18%. Aim: To analyze the correlation of exclusive breastfeeding with aspects of growth and developments in babies. Method: This study used an observational analytic method with a cross sectional design and statistical analysis using Chi Square test. Samples were taken from 62 respondents at the age range of 7-12 months. Data collection was taken through parent interviews. Research instruments were used to evaluate growth, digital baby scale was used to measure height and weight, head measuring tape for head circumference and for development the developmental pre-screening questionnaire (KPSP). The study was conducted on 9 July-31 August 2018 at the Gotong Royong Hospital in Surabaya. Results: Breastfeeding and growth aspects showed significant correlation with p value of p =0.027 (p